Some Solutions to Enhance the Youth’s Social Responsibilities (Global Journal of Human-Social Science, 2024)
The article is based on a number of legal bases regulating the youth s responsibilities and proposes some solutions to enhance their social responsibilities in accordance with the current context The research was conducted on 207 subjects who are officials working in fields related to youth affairs in 5 provinces cities by using questionnaire survey and in-depth interviews Research results show that in the groups of solutions surveyed all are at a good level highly feasible level Among the 4 solution groups the solution group related to training and fostering has the highest mean score and the solution group related to developing legal documents and policies for youth has a lower level However there is not any group of solutions with low feasibility
Keywords: youth; social responsibilities; solutions to enhance social responsibilities